OPTIMIZATION OF SCOUTING EDUCATION IN IMPROVING STUDENT LIFE LEADERSHIP PGSD KANJURUHAN UNIVERSITY OF MALANG - Yulianti dan Muslim (Vicratina : Jurnal Ilmiah Keagamaan, 2016)
Abstract Development of a national character in school is done through activities eksrakurikuler that one of them is scouting, in line with the strategic plan for 2009-2014 is more emphasis on the implementation of the main functions of the Scout Movement as an Institute of Education Kader Nations. But in actual use in school there are several obstacles, among other things because of the voluntary nature of scouting was followed only a handful of students, or if there are schools which require these activities, the results are not too maximum, meaning that only a large quantity alone. This study used a qualitative approach with case study design was observational relating to the activities of Student Creativity Unit (UKM) scout Racana Kanjuruhan Malang. Data collection techniques are: (1) in-depth interviews (2) of participant observation and (3) study the documentation. Research shows that in order to internalize moral values of students to the curriculum in 2013 scouts become one charge ektrakurikuler mandatory for students, then Master SD / MI should have knowledge about education scouts before they become a scoutmaster in elementary school (SD), (2) Education College Scouting in servicing the creativity of the students in developing their talents and interests for status as a student, that student participation is not just a voluntary no necessity PGSD students to follow or be actively involved in SME Scouts. SME cooperation with branch quarter Scout Scout Malang through Scouting Education Orientation (OPP) Basic and Advanced Course (KMD) can motivate students in following the Boy Scouts PGSD well. Keywords: SMEs Scout, Scoutmaster, Student PGSD, Education Scouting